Skrining dan Pemeriksaan pada Lansia - Nurlathifah N. Yusuf; Eka Mustika Yanti; Baiq Disnalia Siswari; Supiani; Dwi Wirastri (Arfah BHMS Foundation, 2026)
The increasing number of productive-age and elderly populations in Indonesia has led to a higher risk of non-communicable diseases (NCDs), while awareness and access to preventive health services remain limited, particularly in rural areas. This community service activity aimed to conduct health screening and examinations as an effort for early detection and to improve community health awareness. A participatory–educative approach was applied through anthropometric measurements, blood pressure assessment, waist circumference measurement, and point-of-care testing for random blood glucose and cholesterol among productive-age adults and elderly residents in Otak Lendang Village, Masbagik District, East Lombok Regency. The results indicated that a considerable proportion of participants had elevated blood pressure, high blood glucose and cholesterol levels, and signs of central obesity, not only among the elderly but also within the productive-age group. These findings suggest that the risk of NCDs has emerged at a younger age and requires serious attention. The implications of this activity highlight the importance of community-based health screening integrated with promotive and preventive education to encourage healthy lifestyle changes. In conclusion, community health screening is effective in the early identification of NCD risk factors and has the potential to serve as a foundation for planning sustainable health interventions at the village level.